Comparison Between Mechanical and Non Mechanical Bowel Preparation Prior To Elective Colorectal Surgery - Altaee, Wissam Jaffar (AL-Kindy College Medical Journal, 2011)
Background: Bowel preparation prior to colonic surgery usually includes antibiotic therapy together with mechanical bowel preparation which may cause discomfort to the patients, prolonged hospitalization and water & electrolyte imbalance. Objective: to assess whether elective colon and rectal surgery may be safely performed without preoperative mechanical bowel preparation. Method: the study includes all patients who had elective large bowel resection at Medical City – Baghdad Teaching Hospital between Feb, 2007 to Jan, 2010. Emergency operations were not included. The patients were randomly assigned to the 2 study groups (with or without mechanical bowel preparation. Results: A total of 165 patients participated in the study, 82 with mechanical bowel preparation and 83 without. The 2 groups were similar in age, sex and type of surgical procedure. 134 patients (81.2 %) underwent surgery owing to colorectal cancer & 31 patients (18.8 %) owing to benign disease. The hospitalization period was longer in the bowel-prepared group (mean ± SD, 8.2 ± 5.1 days) as compared with the non prepared group (mean ± SD, 8.0 ± 2.7 days). However, this difference was not statistically significant. The time until the 1st bowel movement was similar between the 2 groups : a mean ± SD of 4.2 ± 1.3 days in the non prepared group as compared with a men ± SD 4.3 ± 1.1 days in the prepared group ( P = NS ). Conclusion: Our results suggest that no advantage is gained by preoperative mechanical bowel preparation in elective colorectal surgery.